Distance Education Competencies of Physical Education Teachers: Elazığ Province - Altungül, Oğuzhan; Söyler, Didem Yavuz (Tamer KUTLUCA, 2023)
The purpose of this research; The aim of this study is to examine whether the distance education competencies of physical education teachers working in Elazig differ in terms of different variables. The universe of the study consists of physical education teachers working in the province of Elazig in Turkey, while the sample consists of 155 physical education teachers selected by random method. In the research, which was prepared in a 5-point likert type consisting of a personal information form and 18 items, in order to collect data in the research; Physical Education Teachers’ Distance Education Competencies Scale was used. According to the research findings, 69.7% of the participants are male, 52.9% are 36-45 years old, 78.1% are married, 54.8% are at school level, 31.0% are 16-20 years. seen as. When we look at the analysis of variance according to the age and seniority of the participants, it was seen that there was a significant difference between the groups. In conclusion; When the Distance Education Competencies of Physical Education Teachers were examined, it was seen that the distance education competencies of the teachers decreased as the age and professional seniority of the teachers increased.

The purpose of this research; The aim of this study is to examine whether the distance education competencies of physical education teachers working in Elazig differ in terms of different variables. The universe of the study consists of physical education teachers working in the province of Elazig in Turkey, while the sample consists of 155 physical education teachers selected by random method. In the research, which was prepared in a 5-point likert type consisting of a personal information form and 18 items, in order to collect data in the research; Physical Education Teachers’ Distance Education Competencies Scale was used. According to the research findings, 69.7% of the participants are male, 52.9% are 36-45 years old, 78.1% are married, 54.8% are at school level, 31.0% are 16-20 years. seen as. When we look at the analysis of variance according to the age and seniority of the participants, it was seen that there was a significant difference between the groups. In conclusion; When the Distance Education Competencies of Physical Education Teachers were examined, it was seen that the distance education competencies of the teachers decreased as the age and professional seniority of the teachers increased.
Distance Education Competencies of Physical Education Teachers: Elazığ Province
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi